The Economic Implications of Training for Firm Performance - Pedro S. Martins (Global Labor Organization (GLO), 2022)
This paper surveys the emerging economics literature on the relationship between employee training and firm performance. Most studies find very high returns to training, at least from the perspective of firms, indicating that the costs of training can be recouped in short periods of time. These results follow from different identification approaches, including randomised control trials. The training provided is typically of a general nature, which is consistent with employers' labour market power. Several areas for future research are also proposed, including the role of labour market institutions in promoting training and the extent to which the productivity effects of training are shared with employees.
Keywords: M53; I26; J24; 330; Productivity; Skills; Competences; Human Capital; Lifelong Learning; Employment; Public Policy; Programme Evaluation